2022
DOI: 10.3389/fninf.2022.997068
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrid visual stimuli incorporating periodic motions into conventional flickering or pattern-reversal visual stimuli for steady-state visual evoked potential-based brain-computer interfaces

Abstract: In this study, we proposed a new type of hybrid visual stimuli for steady-state visual evoked potential (SSVEP)-based brain-computer interfaces (BCIs), which incorporate various periodic motions into conventional flickering stimuli (FS) or pattern reversal stimuli (PRS). Furthermore, we investigated optimal periodic motions for each FS and PRS to enhance the performance of SSVEP-based BCIs. Periodic motions were implemented by changing the size of the stimulus according to four different temporal functions den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…In terms of accuracy and ITR, a square-shaped flickering and rotating stimuli outperformed a flickering-only stimulus, especially with slow and clockwise rotation [44]. Also, the combination of flicker or patternreversal checkerboard with a grow-shrink stimulus could increase the SSVEP amplitudes, depending on the waveform [59]. However, the combination of flickering and sliding shape stimuli decreased the performance compared to the flickering-only stimulus [76].…”
Section: Stimulus Typementioning
confidence: 96%
“…In terms of accuracy and ITR, a square-shaped flickering and rotating stimuli outperformed a flickering-only stimulus, especially with slow and clockwise rotation [44]. Also, the combination of flicker or patternreversal checkerboard with a grow-shrink stimulus could increase the SSVEP amplitudes, depending on the waveform [59]. However, the combination of flickering and sliding shape stimuli decreased the performance compared to the flickering-only stimulus [76].…”
Section: Stimulus Typementioning
confidence: 96%
“…There are several studies focused on introducing the motion attribute in the low-frequency SSVEP-BCIs for encoding the targets. Kwon et al [33] demonstrated that the conventional SSVEP visual stimuli combined with appropriate periodic motion significantly increases the SSVEP amplitudes, thus improving the SSVEP-BCI performance. Yan and Xu [34] adopted five frequencies to encode nine targets and proposed a BCI method based on light-flashing and motion hybrid coding.…”
Section: Introductionmentioning
confidence: 99%